Responses of differential metabolites and pathways to high temperature in cucumber anther - Chen, Lin; Liang, Zhaojun; Xie, Shuyan; Liu, Wenrui; Wang, Min; Yan, Jinqiang; Yang, Songguang; Jiang, Biao; Peng, Qingwu; Lin, Yu’e (Frontiers in Plant Science, 2023)
Cucumber is one of the most important vegetable crops, which is widely planted all over the world. Cucumber always suffers from high temperature stress in South China on summer. In this study, the liquid chromatography-mass spectrometry (LC-MS) analysis was used to study the differential metabolites of cucumber anther between high temperature stress (HT) and normal condition (CK). After HT, the pollen fertility was significantly reduced, and abnormal anther structures were observed by paraffin section. In addition, metabolomics analysis results showed that a total of 125 differential metabolites were identified after HT, including 99 significantly up-regulated and 26 significantly down-regulated metabolites. Among these differential metabolites, a total of 26 related metabolic pathways were found, and four pathways were significant difference, including porphyrin and chlorophyll metabolism, plant hormone signal transduction, amino sugar and nucleotide sugar metabolism, glycine, serine and threonine metabolism. In addition, pollen fertility was decreased by altering metabolites of plant hormone signal transduction, amino acid and sugar metabolism pathway under HT. These results provide comprehensive understanding metabolic changes on cucumber anther under HT.